Spatial zonation system with Voronoi diagram and Delaunay triangulation to improve management education - Arie Vatresia; Ferzha Putra Utama; Nirwana Nirwana (Intelektual Pustaka Media Utama, 2023)
The zonation system is one of the efforts of the Indonesian Government to improve the quality of education services continuously, but the implementation is still considered less useful. Some areas were still grouped into the different zone from the original. Based on this problem, the solution needed for the zonation mapping of each school so that the apparent zonation limit can be resolved. An application that can map schools in an area based on housing for prospective students is a solution that can be considered at this time. This research showed the implementation of Voronoi diagrams to cluster the area based on the school position within Bengkulu City. The system was also capable of mapping the residential of the student address to match the choice for registration in available secondary school and senior high school. The implementation of the system showed a better result for school zonation over Bengkulu City based on web geographic information system (Web GIS). Furthermore, the comparison analysis over the existing system also showed that the performance of the Voronoi diagram for school zonation the method could solve the problem of the overlapping zonation with Radius method. Three hundred fifty students validated this system to show the performance of this method. The result showed that 72.05% of students matched the first choice, while 27.95% of students matched the second choice. This research showed the analysis of the value of this gap appeared due to the student preferences and school capacity factors.